2018
DOI: 10.1021/acs.jmedchem.8b00824
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Piperazinyl Pyrrolidin-2-ones as a Novel Series of Reversible Monoacylglycerol Lipase Inhibitors

Abstract: Monoacylglycerol lipase (MAGL) is a major serine hydrolase that hydrolyzes 2-arachidonoylglycerol (2-AG) to arachidonic acid (AA) and glycerol in the brain. Because 2-AG and AA are endogenous biologically active ligands in the brain, inhibition of MAGL is an attractive therapeutic target for CNS disorders, particularly neurodegenerative diseases. In this study, we report the structure-based drug design of novel piperazinyl pyrrolidin-2-ones starting from our hit compounds 2a and 2b. By enhancing the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 28 publications
3
74
0
Order By: Relevance
“…However, the 4‐methoxy phenyl part of the ligand is involved in close van der Waals interactions in the hydrophobic atmosphere of Leu148, Leu213 and Leu241. This pattern of binding is in full agreement with the inhibitor bound crystal structures reported earlier (Aida et al., 2018; Bertrand et al., 2010; Labar et al., 2010; Scalvini et al., 2016). In the formalin‐induced nociception test, compound 25 showed a dose‐dependent reduction of pain response in both acute and late phases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the 4‐methoxy phenyl part of the ligand is involved in close van der Waals interactions in the hydrophobic atmosphere of Leu148, Leu213 and Leu241. This pattern of binding is in full agreement with the inhibitor bound crystal structures reported earlier (Aida et al., 2018; Bertrand et al., 2010; Labar et al., 2010; Scalvini et al., 2016). In the formalin‐induced nociception test, compound 25 showed a dose‐dependent reduction of pain response in both acute and late phases.…”
Section: Discussionsupporting
confidence: 91%
“…Glide 5.9 implemented in Maestro 9.4 (GUI of Schrodinger) was used for extra precision (XP) docking of potential ligand (compound 25). The X‐ray crystal structure of h MAGL (PDB ID: http://5ZUN, Resolution‐1.35 Å) was retrieved from Protein Data Bank (PDB) and utilized for molecular docking study (Aida et al., 2018). Protein preparation wizard in Maestro was used for the protein structure preparation like deletion of water molecules, assignment of bond orders, the inclusion of hydrogen atoms and treatment of formal charges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, a selective and reversible inhibitor of MAGL was developed by Takeda Pharmaceutical: compound 34 (Figure 5). 152 This compound with a piperazinyl pyrrolidin‐2‐one structure showed great balance between metabolic stability (29 μL/min/mg) and inhibition activity (IC 50 = 3.6 nM). The authors reported that it was selective against MAGL over FAAH, but selectivity over other serine hydrolases has not been reported yet.…”
Section: Lipogenic Enzymes’ Inhibitorsmentioning
confidence: 99%
“…Among the many nitrogen-containing heterocycles, the pyrrolidinone scaffold is found in a large number of bioactive compounds that possess highly diverse biological properties. For examples, some pyrrolidin-2-one derivatives have been found recently to exhibit good anticancer, 1 antiviral, 2 anticonvulsant, 3 and antioxidant 4 activities, whereas others have been used as reversible monoacylglycerol lipase inhibitors, 5 -adrenoceptor antagonists, 6 and selective orexin-2 receptor antagonists. 7 As a consequence, many new synthetic methods for pyrrolidin-2-ones have been reported over the past decades.…”
mentioning
confidence: 99%